Evaluation of Stress and Anxiety Levels on Science and Engineering Undergraduate Students in Spain When Facing Written Assessments Guides for Positive Interventions - Cordoba-Calquin, C (Academic Press, 2024)
Anxiety and stress disorders are increasingly common, especially among undergraduate students, significantly affecting their family, social, and academic lives. The isolation from restrictive measures during the COVID-19 pandemic in Spain has further exacerbated mental health issues. The disruption of in-person teaching has also impacted traditional learning and evaluation processes, increasing stress and anxiety levels in students. Based on this background, this study aims to analyze the incidence of these disorders among undergraduates and their relationship with various academic, demographic, and family factors, considering the influence of COVID-19. Our results were obtained from a survey conducted among first- and second-year URJC students who are enrolled in an experimental degree program. The statistical analysis provides guidelines for positive interventions to increase student motivation, which further leads to academic success. Results show that women exhibit higher levels of stress and a greater prevalence of anxiety compared to men. The study highlights the influence of specific factors on anxiety levels among students, proposing direct lines of action that enhance positive feelings concerning academic tasks. © 2024 The Authors